2017
DOI: 10.1103/physreve.96.032914
|View full text |Cite
|
Sign up to set email alerts
|

Scaling laws for the mechanics of loose and cohesive granular materials based on Baxter's sticky hard spheres

Abstract: We have conducted discrete element simulations (pfc3d) of very loose, cohesive, granular assemblies with initial configurations which are drawn from Baxter's sticky hard sphere (SHS) ensemble. The SHS model is employed as a promising auxiliary means to independently control the coordination number z_{c} of cohesive contacts and particle volume fraction ϕ of the initial states. We focus on discerning the role of z_{c} and ϕ for the elastic modulus, failure strength, and the plastic consolidation line under quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 42 publications
7
39
0
Order By: Relevance
“…Many current models used for studying snow failure, however, do not consider any healing mechanism or consider only sintering (e.g., Gaume et al, 2017;Reiweger et al, 2009;Steinkogler et al, 2015). Moreover, we showed that if we add viscous deformation and with it load relaxation, the FBM is capable of reproducing the observed loading rate dependence of the snow failure (e.g., larger strain at equal stress, no divergence, and higher τ for low loading rates).…”
Section: 1029/2019gl082382mentioning
confidence: 76%
“…Many current models used for studying snow failure, however, do not consider any healing mechanism or consider only sintering (e.g., Gaume et al, 2017;Reiweger et al, 2009;Steinkogler et al, 2015). Moreover, we showed that if we add viscous deformation and with it load relaxation, the FBM is capable of reproducing the observed loading rate dependence of the snow failure (e.g., larger strain at equal stress, no divergence, and higher τ for low loading rates).…”
Section: 1029/2019gl082382mentioning
confidence: 76%
“…The ice bead samples, in contrast, are rather clustered. Partially this can be explained by looking at the contact density ν c , as resolved in the magnification (Figure 7B), for which an increasing relation with E is expected (Gaume et al, 2017) and seen in the results of the poured samples. For tapped samples, the relation is rather vague, due the uncertainty intervals of all parameters and their small ranges.…”
Section: Relation Between Microstructure and Mechanicsmentioning
confidence: 88%
“…The relation of compressive strength and sintering time (Figure 9) shows the reproducibility of the experiments, despite the large scatter, which however is typical for snow. The requirements for the representative elementary volume (REV) are met for the ice beads with 32 r p and n p ∈ (1, 000, 1, 200) at the lower limit, which was found in 30 r p (Wiacek and Molenda, 2016) or n p ≥ 1, 000 particles (Gaume et al, 2017). In contrast, the requirements are clearly fulfilled for the RG snow samples.…”
Section: Relation Between Microstructure and Mechanicsmentioning
confidence: 93%
See 2 more Smart Citations